RESPONSE OF TROPHIC GROUPS OF MACROBENTHIC FAUNA TO ENVIRONMENTAL DISTURBANCE CAUSED BY FISH FARMING - Sapto P Putro (JOURNAL OF COASTAL DEVELOPMENT, 2009)
Sediment dynamics and the hydrodynamics of the environment cause the complexity and variability inanimal-sediment relationship, both in spatial and temporal. This study is focused on the response ofmacrobenthic fauna to environmental disturbance caused by fish farming using their trophic structure.Their changes in trophic structure can be used as an indicator of disturbance. Eight control sites and eightfarm pontoon sites were samped in a full year period. Two stations at each site were sampled five timesthroughout the year with four replicates. Macrobenthic abundance was categorised based on six majortrophic groups: carnivores (CAR), herbivores (HER), omnivores (OMN), suspension feeders (SF), surfacedeposit feeders (SDF), and subsurface deposit feeders (SSDF). The Infaunal Trophic Index (ITI) andShanon-Wiener diversity index (H’) were used to assess the degree of environmental disturbance caused byfish farming based on trophic structure. The relationship between ITI and H’ was assessed usingSpearman’s rank order correlation (rho). The result showed that the abundance of deposit feeders wassignificantly higher at the farm sites than at the control sites, suggesting that food availability is morevaried and abundant at farm sites than those at control sites. The results of the ITI indicate that the entiresampling sites have been moderately disturbed over the sampling period, with the exception for site BC8.Variability of Shanon-Wiener diversity index (H’) spatially and temporally seems co-vary with ITI, owing tothe influence of taxa richness and evenness.